The dilemma of managing scarce health care resources: Evidence of the conflict between economic and ethical principles in microallocation decisions - Micaela M. Pinho (The International Journal of Management Science and Information Technology (IJMSIT), 2014)
Health economists proposed maximizing additional health gains as a criterion to set priorities and to maximize social welfare in the microallocation of healthcare resources. This requires that social values from health improvements are neutral in relation to personal characteristics of people, which seems to be often contradicted by empirical evidence. This paper addresses the social and ethical values that can potentially conflict with economic ones in decisions taken at the micro level of healthcare rationing. Using quantitative and qualitative data collected from a random sample of 200 college students we explore their (i) orientations and motivations when faced with hypothetical scenarios involving prioritization of patients that are distinguished only by their personal characteristics and (ii) views concerning its involvement in decision making over which patients to treat. Findings suggest: (i) the coexistence of fairness and economic orientations among respondents even though utilitarianism received the greatest support; (ii) that although respondents wish to be consulted in matters of microallocation decisions, they do not want to assume the role of deciding between patients
Keywords: 650; Microallocation; Efficiency; Ethical judgments